The future of innovation in e-learning - Noura Saleh Al-Bhijan; Hessa Abdullah Al-Suraibi; Haila Abdul-Aziz Al-Mansour (International Journal of Computers and Informatics, 2026)
This study explores the foresight of e-learning’s future as a scientific vision aimed at avoiding past errors and constructing innovative educational models. The source examines global transformations triggered by the COVID-19 pandemic, which accelerated digital transformation and the adoption of advanced technologies such as Learning Management Systems (LMS) and adaptive learning. Furthermore, the study focuses on modern trends, including the integration of Artificial Intelligence (AI), Virtual Reality (VR), and mobile learning to personalize learner experiences and enhance educational quality. The findings underscore the significance of micro-credentials and flexible learning pathways in supporting lifelong learning and aligning education with labor market demands. Despite vast technological opportunities, the study identifies core challenges, most notably ensuring digital equity and justice, protecting privacy, and updating curricula to keep pace with rapid changes. The study concludes by recommending the support of innovative and institutional initiatives to ensure the future sustainability of digital education.